Proteksi Minat dan Motivasi Belajar Aud Selama Masa Pandemi Covid 19 di RA Hidayatullah Medan Marelan - Sakinah Siregar; Rahmi Intan Sari; Dewi Handayani; Dewi Sartika (Sekolah Tinggi Agama Islam Sumatera Medan, 2020)
This study aims to analyze 1) The causes of decreased interest and motivation for early childhood in participating in learning, (2) various forms of behavior that reduce the interest and motivation of early childhood, (3) Solutions for handling decreased interest and motivation of early childhood. The research method used is a qualitative method, with data collection techniques used are observation, interviews, and documentation, all of which are done online. The results of this study are the Variety of Behavioral Forms of Decreasing Interest and Motivation of early childhood RA Hidayatullah Medan Marelan, namely: (1) Not enthusiastic about learning, (2) Tired of learning, (3) Disobedient or not following teacher orders, (4) Not follow or not follow the lesson. Meanwhile, solutions to reduce early childhood interest and motivation are (1) intense dialogue with parents and related students, (2) packaging learning with play activities, (3) special interest classes once a week, (3) visiting student home teachers, (4) Multi-Dialogue.